Edukasi Kebiasaan Cuci Tangan pada Anak Pra Sekolah Sebagai Upaya Menurunkan Kejadian Diare di TK ABBA Sunan Gunung Jati - Dias Utami , Khristina; Susanti , Dwi; Lutfiyati , Afi; Ferianto (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Diarrhea is the second cause of childhood mortality after pneumonia. Globally, diarrhea affects 525.000 (0,030%) children, moreover it has impacted almost 1,7 billion yearly (WHO, 2017). The prevalence in Indonesia has reached to 182,3 (6,2%) among 5-14 years old. In Daerah Istimewa Yogyakarta, the diarrheal disease has always been among the 10 biggest pediatric disease, especially in preschool students are account for 8,47%. The high numbers of diarrheal diseases caused by several factors, one of them is a lack of awareness in wash hand using soap. Educational activity for diarrheal disease and wash hands using soap was conducted in TK Islam Sunan Gunung Jati Kasihan Bantul. The result from this questionnaire shows the majority of students in 6 years old are 59,7%, female students was noted in 57,9%, students that are diarrhea-free in the past 3 months are 87,7%, and students that always wash their hands are 63,2%. This activity used a video as a learning media with 6 steps to wash your hand from WHO, along with the demonstration to wash hands with soap. The result of this education is the students able to answer several questions after the activity. It approves that education use video and hand-wash demonstrations with soap, improves the students’ awareness to prevent diarrhea in children.